Efektivitas Sistem E-Budgeting dalam Memitigasi Resiko Penyelewengan Anggaran pada Pemerintah Kota Surabaya - Nadhira Allysha Rahmania; Jelita Nur Aziza; Eva Hany Fanida; Revienda Anita Fitrie (Journal Social Society, 2026)
This research is motivated by the vulnerability of regional budget preparation processes to corruption, collusion, and nepotism (KKN), such as “phantom budgets” and budget manipulation caused by manual, non-transparent systems. This study aims to evaluate the effectiveness of the E-Budgeting system in the Surabaya City Government as a tool to mitigate the risk of budget misappropriation. Using a qualitative descriptive method, the research analyzes secondary data from official financial reports and BPK audit results through documentation and literature studies. The results indicate that E-Budgeting in Surabaya effectively mitigates budget fraud risks by digitizing every stage of planning from Musrenbang to APBD and locking data inputs to prevent unauthorized changes. Features such as the audit trail strengthen internal control and transparency, contributing to Surabaya’s consistent Unqualified Opinion (WTP) from the BPK. However, the system’s effectiveness remains dependent on non-technical factors, including the integrity of human resources and institutional commitment. The study concludes that while E-Budgeting significantly narrows the opportunity for administrative fraud, continuous training and supervision are essential for optimal implementation.